(untitled) (Legal journal - Research in Legal and Social Sciences, 2020)
The Public Ministry’s Training Centre, in compliance with the Institutional Strategic Plan, asseses the impact of its training program. In this sense, the Training Centre has reviewed the results of the developed activities in the program named: organized crime, class 2019. The objective was to strengthen the knowledge and skills of the institutions’ servanst who step in the fight against the organized crime. The institutions that took part as organizers were: CEMP, CIMEE and ISEPOL, and the guest institutions were: SEPRELAD, SENAD and SENABICO. The methodology was a mixed approach with a correlation level, a deductive method was applied, the program’s strenghts and weaknesses were also analyzed. The population consisted of 48 graduates and the sample of 38, which represents the 79,2 % of the total. The data collection was made by an online form with 16 items. With regard to the results, it highlights the development of critical thinking, the formation of sustainable opinions, the ability to harmonize theories in dissent, the enhancement of team work and the importance of the cooperation as an estrategy to optimize the State’s resources, foster transparency, fight againstcorruption and finally be able to firmly get involved in the fight against this problem. The study made possible to obtain information about the students, by assesing the usufulness and relevance of the traineeship in their daily tasks, the incidence of sharing with other team members of the main institutions that work in the area.